Gambaran Post Traumatic Growth Pada Pasien Kanker Serviks Paska Histerektomi - Robertus Surjoseto; Devy Sofyanty (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
Cervical cancer is a gynecology disease and primarily cause of woman death, hysterectomy is a surgical procedure to remove partially or totally the uterus. Hysterectomy is one of the surgical actions that causes anatomical changes. This research aims to examine the dynamics on overview of post traumatic growth emergence women with servical cancer post hysterectomy. This study used a qualitative approach three participants who were joined this study were gained by purposive sampling method. Data obtained through observation and interview with subject and significant others. The data collection technique is interview with general guidelines. The study subjects were three early adult woman 30-45 years old, who have hysterectomy between 1-2 years in the Obstetrics and Gynecology Clinic Cipto Mangunkusumo Hospital, Jakarta. Results showed in the process of post traumatic growth, all subjects demonstrated positive change toward higher level of change in perception, relation with others and change in philosophy of life. Change in philosophy of life was found to be the most dominant dimension. Subjects can develop themselves toward psychological growth which is better than ever. This process is also influenced by the presence of presence of social support and believe in God